Characterization of garden soil pollution in the mining village of Stratoni, N. Greece - Argyraki, A.; Plakaki, A.; Godelitsas, A. (Bulletin of the Geological Society of Greece, 2007)
Complete characterization of soil pollution in sulphide ore mining areas can assist risk assessment because the potential human health risk from chemical species intake is related not only to the total content of elements in soil but also to the type of bounding of elements to solid phases and their solubility. The methodology of this study included a combination of chemical analysis and mineralogical determination of surface soil samples from house gardens and communal country spaces in a mining village of north Greece. The content of soil Pb, Zn, Cu, Cd, Fe and Μη was determined by sequential extraction with 5 operational stages and subsequent measurement by AAS. The produced chemical data were coupled by XRD and SEM-EDS mineralogical analysis. Results show variety of solid phases withholding the metals, thus differentiation of metal mobility/ availability in the environment. Lead has high mean concentration of 1090 μg g’1 but is fractioned mostly (53%) in the residual phase of less soluble soil components limiting its potential bioavailability. Zinc, Cd and Mn with means of 878 μg g , 6 μg g’1 and 4465 μg g’1 respectively, participate in appreciable proportion (5-25%) in easily extractable phases indicating easy mobilization and greater potential bioavailability.